CAUDELLA BIPOLARIS SP. NOV. (MICROTHYRIACEAE) ON BREDEMEYERA FLORIBUNDA (POLYGALACEAE) FROM THE BRAZILIAN CERRADO - PEREIRA, O. L.; FILARDI, F. L. R. (Edinburgh Journal of Botany, 2006)
Caudella bipolaris sp. nov. (Microthyriaceae), found on leaves of the liana Bredemeyera floribunda Willd. (Polygalaceae) from the Brazilian cerrado, is described and illustrated. This is the fourth known Caudella species and the first reported on a member of the family Polygalaceae. Unique within the genus are the species' bipolar ascospore appendages.
Keywords: Ascomycota; Dothideomycetidae; foliicolous fungi; Microthyriales; tropical fungi